2020
DOI: 10.1002/cta.2773
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental validation of parasitic capacitance effects on emulated bioimpedance measurements with high‐impedance residuals

Abstract: SummaryParasitic capacitances and high‐residual impedances (typical of electrode/tissue interfaces) have significant effects on estimated electrical impedances of tissues under study. This leads to deviations (especially at high frequency) from the true tissue impedance. This work outlines the circuit theory describing estimation errors occurring when one and two parasitic capacitances are present in tetrapolar electrode configurations typical for bioimpedance measurements. The described circuit theory was val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, parasitic capacitances introduce errors to experimentally measured variables. Systematic errors caused by leakage currents can be compensated throughout the signal's analog processing stage if the measurement system is properly calibrated and known [41,51]. In addition, one would also observe in some situations at high frequencies, in a range reaching the usable limit of 1 MHz in EIT systems, certain effects that could be interpreted as parasitic effects of an interplay of inductive and capacitive nature [52].…”
Section: Excitation Current Compensationmentioning
confidence: 99%
“…However, parasitic capacitances introduce errors to experimentally measured variables. Systematic errors caused by leakage currents can be compensated throughout the signal's analog processing stage if the measurement system is properly calibrated and known [41,51]. In addition, one would also observe in some situations at high frequencies, in a range reaching the usable limit of 1 MHz in EIT systems, certain effects that could be interpreted as parasitic effects of an interplay of inductive and capacitive nature [52].…”
Section: Excitation Current Compensationmentioning
confidence: 99%
“…To exploit the potential of this nowadays’ new technique, many technological barriers still need to be eliminated 10 – 12 . As far as difficulties emerging with the employment of the technique are concerned, a further, almost impenetrable problem is that the effects of the measurement artifacts also depend on the unknown impedance itself 13 . A thorough review of the international literature revealed, that the measurement methodology and the mathematical methods generally implemented in the data evaluation procedure, as well as other efforts to improve BI-based technologies have not fulfilled the expectations yet 11 , 14 .…”
Section: Introductionmentioning
confidence: 99%